Single-cell profiling transcriptomic reveals cellular heterogeneity and cellular crosstalk in breast cancer lymphatic node, bone, and brain metastases - Longyu Zhu; Miaomiao Liu; Yuguang Shang; Jingge Cheng; Hongye Zhao; Jun Zhang; Dongxing Shen (Scientific Reports)
Abstract Breast cancer is the most common malignant tumor in the world, and its metastasis is the main cause of death in breast cancer patients. However, the differences between primary breast cancer tissue and lymphatic node, bone, and brain metastases at the single-cell level are not fully understood. We analyzed the microenvironment heterogeneity in samples of primary breast cancer (n = 4), breast cancer lymphatic node metastasis (n = 4), breast cancer brain metastasis (n = 3), and breast cancer bone metastasis (n = 2) using single-cell sequencing data from the GEO database. The malignant epithelial cells were characterized by InferCNV algorithm. The cell-cell communication was analyzed using CellChat package. The biological function of cell subpopulations was analyzed using gene set variation analysis. The expression of STMN1 was analyzed using immunohistochemical staining. The proportion of pCAFs in breast cancer was explored using multispectral immunohistochemical staining. We identified seven cell clusters in primary and metastatic breast cancer (Lymphatic node, brain, and bone metastases) by analyzing single-cell transcriptomic profiles. T-NK and B cells dominated breast cancer with lymphatic node metastasis, whereas fibroblasts were prevalent in brain metastases and primary breast cancer. We identified five T cells (T memory, CD8 + T cells, regulatory T cells, natural killer cells, CD4 + T cells), three B cells (naïve B cells, memory B cells, plasma B cells), and five cancer-associated fibroblasts (CAFs) subpopulations (Smooth muscle cells (SMC), pericyte, antigen-presenting CAFs (apCAFs), proliferative CAFs (pCAFs), and matrix CAFs (mCAFs)). Notably. pCAFs dominated breast cancer with lymphatic node, bone, and brain metastasis. Furthermore, we identified four malignant epithelial cell subpopulations: G0, G1, G2, and G3. The G2 cell population exhibited strong invasion ability, it can differentiate into G3 with strong proliferative ability and proliferation-related G1 cell population after metastasis. Cell-cell communication demonstrated an interaction between pCAFs and metastasis-associated malignant epithelial cells. Finally, we discovered that in advanced breast cancer, the proportion of pCAF increased and was associated with a poor prognosis of breast cancer. This study elucidated the potential cellular origins and drivers of breast cancer metastases to lymphatic nodes, brain, and bone, utilizing single-cell transcriptomic profiles. Furthermore, it demonstrated that increased pCAFs were associated with advanced breast cancer and a poor prognosis.